Polymeric composite based on waste material for high voltage outdoor application - Aman, Aminudin; Ibrahim, Khairul Anwar (Elsevier, 2013)
This paper presents the preparation of artificial reinforcement filler for polymeric composite insulation for high voltage outdoor application. The purpose of this study is to examine the possibility of waste material as filler for polymeric composite insulation that beneficial to our environment and economy. For this composite, a seashell (CaCO3) and waste glass (SiO2) were selected to produce an artificial wollastonite (calcium silicate-CaSiO3) that use as filler and Polypropylene (PP) is utilized as a matrix. X-ray diffraction (X-RD) technique is applied to reveal the chemical composition of an artificial wollastonite (AW). Preparation method via melt compounding using a Haake internal mixer and a response surface methodology (RSM) statistical technique is used for sample preparation. Then, breakdown test complying with BS EN 60243-1:1998 is adopted to examine the breakdown strength of this newly polymeric composite. It was found that chemical compositions of the proposed materials similar with naturally wollastonite (calcium silicate-CaSiO3) and the optimum compound is at 65/35 PP–AW wt% with 14.76 kV/mm breakdown strength. A step of processes to produce an artificial wollastonite (AW) is presented in this paper.